POLITICAL COMMUNICATION OF CHRISTIAN LEGISLATIVE CANDIDATES IN ISLAMIC-BASED VOTERS: A STUDY OF THE LEGISLATIVE GENERAL ELECTION IN INDONESIA REFORMED ERA OF 1999-2019 - Chontina Siahaan, Osbin Samosir, Hapzi Ali (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to analyze the political communication of Christian legislative candidates in Islamic- based voters. Christian political parties in the five election periods in the Reformation Era, 1999, 2004, 2009, 2014, and 2019 always got significant voting percentage nationwide, both in the electoral district where Christian was a majority or not. The most significant percentage of voters of Christian parties were from West Java province, a robust Islamic province with substantial issues on religious identity politics, especially in the 2014 and 2019 elections. One of the political parties that always gains victory in Islamic based districts in West Java is the Partai Demokrasi Indonesia-Perjuangan (PDI-P). The success is inseparable from the political communication of Christian legislative candidates in the constituencies. The theory used in this article is the Symbolic Interaction theory. The methodology is descriptive qualitative by explaining how the phenomenon of communication that occurs between Christian legislative candidates and the voters in the Islamic-based electoral district. The findings of this study are that the political communication of candidates for the Christian legislature uses a cultural approach to religion and local culture by approaching through the local cultural and religious orders, several local figures, i.e. religious, community leaders and government leaders; and through free medication service, development of infrastructure facilities such as mosques, provision of drinking water, and roads.